Medication Adherence and Practices in Pediatric Patients - Sweta Shanbhag; Shreedhara Avabratha K; Sudhir Prabhu H; Bhagyalakshmi K (Research Center for Rational Use of Drugs (RCRUD), 2024)
Background: Improper medication practices and non-adherence are the biggest challenges faced by pediatricians in outpatient practice. Hence this study was aimed at determining the medication practices and factors affecting adherence. Methods: A cross sectional descriptive study was conducted at a tertiary care hospital in Southern India over a period of 3 months (January to March 2023), to study medication adherence and parental medication practices in pediatric patients. A pre structured questionnaire was administered to parents of 320 children. Results: Majority of the parents (55%) had children aged 1-5 years of age. It was noted that most of the families (89%) were above poverty line (APL). About 34% parents were educated till graduate level and 17% were educated beyond post graduate level. Frequency of medication adherence in our study was found to be 78%. It was noted that parents with education of graduate level and above, those belonging to APL families and the ones with no fear of adverse drug reactions showed higher medication adherence as compared to other parents and this association was found to be statistically significant (p <0.001). Majority of the parents (80%) reported that their children preferred liquid formulations, of which 57% preferred fruit flavoured ones. Around 51% parents preferred twice daily dosing of medications. While 47% parents used previous prescriptions, 39% bought over the counter medicines, especially paracetamol. Conclusion: Knowledge about medication practices and factors affecting adherence is important in order to provide quality health care. Actively involving children and parents while prescribing medications with health education goes a long way in improving adherence.